MEDIA SOSIAL SEBAGAI MEDIUM KOMUNIKASI DAKWAH - Suharto Suharto (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
Indonesia is listed as the country with the most Twitter users in the world in 2010, more precisely amounted to 20.8% of internet users in the country or about 45 million Indonesians. The users of social media use twitter as a medium of da’wah (islamic preaching). Utilizing social media as a medium of da’wah means to affirm the existence of a preacher to always preach and transmit religious messages without being constrained by space and time. With social media facilities, a preacher also can make time efficient to interact with the audiences and sort content of da’wah which is more recent and fun.